2008
DOI: 10.4049/jimmunol.181.7.4648
|View full text |Cite
|
Sign up to set email alerts
|

Swift Entry of Myelin-Specific T Lymphocytes into the Central Nervous System in Spontaneous Autoimmune Encephalomyelitis

Abstract: Strong evidence supports that CNS-specific CD4+ T cells are central to the pathogenesis of multiple sclerosis and experimental autoimmune encephalomyelitis (EAE). Using a model of spontaneous EAE, we demonstrated that myelin basic protein (MBP)-specific CD4+ T cells up-regulate activation markers in the CNS-draining cervical lymph nodes at a time when there is no T cell activation anywhere else, including the CNS, and before the appearance of clinical signs. In spontaneous EAE, the number of MBP-specific T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 51 publications
5
85
0
2
Order By: Relevance
“…It is well described that in EAE, the CNS suffers a massive infiltration by activated lymphocytes, namely CD4 effector T cells, which break the blood-brain barrier and recruit other proinflammatory cells to the site of inflammation, leading to an increased severity of the disease (64). We found that anti-CD4-treated mice did not show any significant infiltrates in the CNS while presenting a reduction of MOG-specific TCR-transgenic cells in the cervical lymph node (the number of nontransgenic CD4 cells did not change, confirming the nondepleting nature of the mAb used).…”
Section: Discussionmentioning
confidence: 99%
“…It is well described that in EAE, the CNS suffers a massive infiltration by activated lymphocytes, namely CD4 effector T cells, which break the blood-brain barrier and recruit other proinflammatory cells to the site of inflammation, leading to an increased severity of the disease (64). We found that anti-CD4-treated mice did not show any significant infiltrates in the CNS while presenting a reduction of MOG-specific TCR-transgenic cells in the cervical lymph node (the number of nontransgenic CD4 cells did not change, confirming the nondepleting nature of the mAb used).…”
Section: Discussionmentioning
confidence: 99%
“…The current findings are also consistent with similar studies using other inflammatory models with a high degree of peripheral lymphatic drainage to the CLNs. For example, surgical excision of the CLNs delayed the onset and reduced clinical disease in the neuroinflammatory model of experimental autoimmune encephalomyelitis (35,36), and cervical lymphadenectomy dramatically reversed corneal allograft rejection to a survival rate of 92% compared with 0% survival noted in the eyes of mice with intact CLNs (37).…”
Section: Cd11bmentioning
confidence: 99%
“…In EAE, myelin-specific T cells are activated in the periphery and migrate into the CNS by crossing the blood-brain barrier (30,31). To investigate if the decreases in disease activity and CNS infiltration and preserved myelin observed in Aif-1-deficient mice (Figures 1-3 Figure S2B), FACS analysis failed to find significant genotype-dependent differences in T-cell subsets.…”
Section: Aif-1 Promotes Expansion and Activation Of Encephalitogenic mentioning
confidence: 99%